2014
DOI: 10.1111/jpi.12127
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin inhibits MUC5AC production via suppression of MAPK signaling in human airway epithelial cells

Abstract: Mucus acts as a primary defense system in the airway against various stimuli. However, excess mucus production causes a reduction in lung function via limitation of the airflow in the airway of patients suffering from asthma or chronic obstructive pulmonary disease (COPD). In this study, we evaluated the effects of melatonin on the production of MUC5AC, a major constituent of the mucin that is secreted from the airway, using epidermal growth factor (EGF)-stimulated NCI-H292 cells, a human mucoepidermoid carcin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 36 publications
5
44
1
1
Order By: Relevance
“…Regulation of MAPKs by Mel has been observed in several cell types, including the CRL 1999 and NCI-H292 cells, where Mel has been reported to inhibit the phosphorylation of ERK1/2 and JNK (c-Jun N-terminus kinase) 29,30. Surprisingly, we found that Mel therapy efficiently reduced the expression of p38 MAPK, p-AKT, and mTOR in OC cells.…”
Section: Discussionmentioning
confidence: 49%
“…Regulation of MAPKs by Mel has been observed in several cell types, including the CRL 1999 and NCI-H292 cells, where Mel has been reported to inhibit the phosphorylation of ERK1/2 and JNK (c-Jun N-terminus kinase) 29,30. Surprisingly, we found that Mel therapy efficiently reduced the expression of p38 MAPK, p-AKT, and mTOR in OC cells.…”
Section: Discussionmentioning
confidence: 49%
“…For collection of BALF, the mice were sacrificed 24 h after AHR measurement with an intraperitoneal injection of phenobarbital (50 mg/kg; Hanlim Pharm., Co., Ltd., Seoul, Korea), and tracheotomy was performed as described previously (9). The lung was lavaged three times, and each time, fluid was withdrawn via the trachea with 0.5 ml PBS (total volume, 1.5 ml).…”
Section: Collection Of Bronchoalveolar Lavage Fluid (Balf) Andmentioning
confidence: 99%
“…Такие эф фекты могут быть тесно связаны с ингибированием фосфорилирования MAPK. Результаты исследова ния показывают, что мелатонин может представлять собой потенциальное лекарственное средство в те рапии хронических заболеваний дыхательных путей, таких как БА и ХОБЛ [43].…”
Section: резюмеunclassified